The influence of instagram marketing, brand ambassador and brand image towards customer satisfaction and customer loyalty on scarlett whitening product - Meidhita Meissy Amalia; Gusti Noorlitaria Achmad (Faculty of Economics and Business Mulawarman University, 2023)
This study aims to determine the effect of Instagram Marketing, Brand Ambassador, and Brand Image towards Costumer Satisfaction and Customer Loyalty on Scarlett Whitening Product. The data analysis tool used in this study is Partial Least Square with the help of SmartPLS 3.0 software. This research was conducted on people in the city of Samarinda who know and use Scarlett Whitening Product that were discovered by researchers by accident. This study uses a quantitative approach. This study used a sample of 105 respondents. The results of this study indicate: (1) Instagram Marketing has a positive and insignificant effect on Customer Satisfaction. (2) Brand Ambassador has a positive and significant effect on Consumer Satisfaction. (3) Brand Image has a positive and significant effect on Customer Satisfaction. (4) Instagram Mareketing has a positive and insignificant effect on Customer Loyalty. (5) Brand Ambassador has a positive and significant effect on Custome Loyalty. (6) Brand Image has a positive and significant effect on Customer Loyalty. (7) Customer Satisfaction has a positive and significant effect on Customer Loyalty.